Respuesta :
If you would like to find the roots of the function f(x) = x^2 - 2 * x - 3, you can calculate this using the following steps:
f(x) = x^2 - 2 * x - 3 = (x - 3) * (x + 1)
1. x = - 1
2. x = 3
The missing number would be 3.
f(x) = x^2 - 2 * x - 3 = (x - 3) * (x + 1)
1. x = - 1
2. x = 3
The missing number would be 3.
The missing value is 3 because roots of the function f(x) = x2 – 2x – 3 are -1 and 3
What is a quadratic equation ?
Any equation of the form [tex]\rm ax^2+bx+c=0[/tex] where x is variable and a, b, and c are any real numbers where a ≠ 0 is called a quadratic equation.
As we know, the formula for the roots of the quadratic equation is given by:
[tex]\rm x = \dfrac{-b \pm\sqrt{b^2-4ac}}{2a}[/tex]
We have a function:
f(x) = x² – 2x – 3
Equate the function to zero;
f(x) = 0
x² – 2x – 3 = 0
a = 1, b = -2, c = -3
[tex]\rm x = \dfrac{-(-2) \pm\sqrt{-2^2-4(1)(-3)}}{2(1)}[/tex]
After simplification:
[tex]\rm x = \dfrac{2 \pm\sqrt{16}}{2}[/tex]
x = 3 or x = -1
Thus, the missing value is 3 because roots of the function f(x) = x2 – 2x – 3 are -1 and 3
Learn more about quadratic equations here:
brainly.com/question/2263981
#SPJ5